COMPARATIVE ANALYSIS OF PRODUCTION RESULTS AND INCOME OF PARTNER RICE FARMERS WITH NON-PARTNERS - Setia Budi; Eva Wardah; Muhammad Zamzami (RADJA PUBLIKA, 2022)
One of the goals of Indonesia's agricultural development is to realize food security through increasing production yields as well as increasing the income of the main actors (farmers) in agricultural development. This study aims to analyze the differences in production and income of lowland rice farming by farmers who are involved in the agricultural extension partnership program with farmers who are not involved in the partnership program by using different technology packages in North Aceh Regency. Analysis of the data used is the T test of two unrelated samples (Independent Samples T Test). The results of the study showed that there were differences in the production and income of the partner farmers of the agricultural extension program at the research location as much as 7,369.44/Kg/MT/Ha with an income of Rp. 21,352. 800 MT/Ha while the production of non-agricultural extension partners is 6,004.28Kg/MT/Ha with an income of Rp. 13,678,100 MT/Ha. The calculated T value for production is 440, 87 and the T table is 1.993 while the T calculated income is 33,214 and the T table is 1,993. Farmers who are members of the agricultural extension partnership program have higher production and income than non-partner farmers.